Status of Islam and immigration in Europe: There case studies - Ramírez, Angeles; Mijares, Laura (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The aim of this article is to analyze the status of Islam in three European countries: France, Holland and Spain. Our work has been framed within the immigrant integration policies of these European states. This approach to the status of Muslim religionis based on the fact that in these three countries all the issues and aspects related to Muslim people are negotiated within the frame of policies directed to immigrant people more than to religious minorities.
Keywords: Immigration; Islam; Integration policies